FARMERS' PERCEPTIONS ABOUT FEED BANK STRATEGIES IN THE ANDINI MULYO PEOPLE'S LIVESTOCK CENTER (SPR), PAPAR DISTRICT, KEDIRI DISTRICT, EAST JAVA PROVINCE - Amalyadi, Rezki (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2024)
This community service aims to find out farmers' perceptions about feed banks carried out at community livestock centers (SPR). Perceptions are used as a reference in developing feed bank strategies for farmers. The data used are primary data and secondary data. Primary data was obtained from village programs while secondary data was obtained from interviews and questionnaires. The data obtained was analyzed using descriptive techniques. Respondents' perceptions of the Feed Bank strategy are classified as very good (60.5), meaning that the Feed Bank strategy has relative advantages, is appropriate, simple, can be tried and can be observed. Characteristics that are related to respondents' perceptions are age and length of farming. Young respondents (28-34 years) tend to have very good perceptions. Respondents whose farming period is new (1-10 years) tend to have very good perceptions.